2012
DOI: 10.3109/10428194.2011.643406
|View full text |Cite
|
Sign up to set email alerts
|

Activity of topotecan 21-day infusion in patients with previously treated large cell lymphoma: long-term follow-up of an Eastern Cooperative Oncology Group study (E5493)

Abstract: The purpose of this study was to determine the activity of topotecan given by 21-day continuous infusion in patients previously treated with one prior therapy for a diffuse large cell lymphoma or immunoblastic lymphoma. Patients with appropriate histology and measurable disease who had been treated with one prior chemotherapy regimen were eligible for study. Slides of tumor biopsies were submitted for central review of pathology. Patients were required to have ECOG performance status of 0, 1, or 2 and adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In addition, TTR does not require aggressive hydration and therefore can be easily given in the outpatient setting. TTR produced an ORR of 69% and CR rate of 42%, which compares favourably to our previous experiences with paclitaxel and topotecan, alone and in combination (Table IV) (Preti et al, 1995;Arbuck et al, 1997;Younes et al, 1997Younes et al, , 2001Kewalramani et al, 2004;Mey et al, 2006;Wiernik et al, 2012). The addition of rituximab in the current study also improved the ORR in patients with primary refractory or relapsed disease.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, TTR does not require aggressive hydration and therefore can be easily given in the outpatient setting. TTR produced an ORR of 69% and CR rate of 42%, which compares favourably to our previous experiences with paclitaxel and topotecan, alone and in combination (Table IV) (Preti et al, 1995;Arbuck et al, 1997;Younes et al, 1997Younes et al, , 2001Kewalramani et al, 2004;Mey et al, 2006;Wiernik et al, 2012). The addition of rituximab in the current study also improved the ORR in patients with primary refractory or relapsed disease.…”
Section: Discussionsupporting
confidence: 88%
“…They proposed that a minimum threshold of the drug must be maintained over long periods for optimal antitumor activity; higher dose-intensity did not provide further benefit, but it enhanced toxicity. Several phase 1 clinical trials of low-dose continuous infusions, including 1 to over 9 weeks of CPT-11, yielded steady-state levels of SN-38 of ∼3 to 15 nM, confirming the tolerability and feasibility of low, protracted dosing. Similar phase 1 trials of continuous infusions of the topo 1 inhibitor topotecan also showed activity in several tumors, again suggesting that efficacy may be achieved by time-over-target inhibition. Thus, topo 1 inhibitors may display exposure-time-dependent rather than concentration-dependent cytotoxicity: achieving a high inhibitor concentration for a short period does not necessarily produce the same effect as maintaining a low concentration for a prolonged period, even if the total AUC per treatment period are equal.…”
Section: Discussionmentioning
confidence: 79%
“…The camptothecin analogue [1] topotecan is utilized for the treatment of malignancy, such as ovarian cancer [2][3][4][5][6][7], cervical cancer [5,[8][9][10], retinoblastoma [11][12][13], small cell lung cancer [14][15][16][17][18], hematopoietic cell malignancy [19,20] and Wilms' tumor [21]. It is applied at a dosage of 10 mg/kg b.w.…”
Section: Introductionmentioning
confidence: 99%